Public perception of crisis in companies: An evaluative study of impact of crisis on brand image and reputation - Jain, Suparna; Singh, Pavitar Parkash; Lakhanpal, Sorabh; Gupta, Manish (Linguistics and Culture Review, 2021)
Crisis is inevitable and in today’s scenario with the pandemic affecting every aspect of our lives, crisis has become something which every industry has had to deal with. The more important aspect today is, how to deal with crisis today. To do so it becomes necessary to understand and evaluate the impact it has on the brand. The study focuses on the impact of crisis on brand image and reputation. The study was conducted amongst the people of Jalandhar with a sample of 130. This study aims at evaluating the relation between a company and it consumers, the way they perceive business news and the manner in which they react to crisis by continuing to support the brand and purchasing.